Dealing with Literature Review and Epistemological Underpinnings in Grounded Theory Methodology - Ndiaga Niasse (CV. Literasi Indonesia, 2022)
The purpose of this paper is to review the crucial debate about undertaking a literature review and adopting an epistemological position in doing a grounded theory study. By relying on existing knowledge about the subject, three main Grounded Theory Approaches are discussed: Glaserian, Straussian, and Constructivist Grounded Theory Methodology. All of them differ somewhat both in adopting an epistemological stance that fits well with their research strategy and conducting a literature review at the earlier stages of the research process. The paper contributes to enhancing knowledge about Glaser’s dictum of ‘getting started’ which seems to be misunderstood by those who still misunderstand the Grounded Theory Methodology (GTM) orthodoxy version.